2004
DOI: 10.1002/chin.200436176
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid and Its Derivatives as anti‐Angiogenic Agents.

Abstract: Terpenes Terpenes U 0200 Betulinic Acid and Its Derivatives as anti-Angiogenic Agents. -Compound (Ib) is reported to possess both antitumor and anti-angiogenic activity. -(MUKHERJEE, R.; JAGGI*, M.; RAJENDRAN, P.; SIDDIQUI, M. J. A.; SRIVASTAVA, S. K.; VARDHAN, A.; BURMAN, A. C.; Bioorg. Med.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 1 publication
3
25
0
Order By: Relevance
“…Tests with SK-MEL-2 and M14-MEL lines showed that the acetylation of hydroxyderivatives causes either a small decrease or no change in cytotoxicity (Kim et al, 2001). This fact is in good agreement with the work, where the influence of the 3-O-acetyl group on cytotoxicity of broader group of triterpenoides 65 -67 was studied (Mukherjee et al, 2004;Sarek et al, 2005). In the work of Chien et al, the cytotoxicity of natural 3-O-acyl derivatives of betulinic acid 68 -71 isolated from Strychnos vanprukii Craib was investigated against MEL2 line.…”
Section: Derivatization Of Betulinic Acid (1) and Betulin (3) In Posisupporting
confidence: 85%
See 1 more Smart Citation
“…Tests with SK-MEL-2 and M14-MEL lines showed that the acetylation of hydroxyderivatives causes either a small decrease or no change in cytotoxicity (Kim et al, 2001). This fact is in good agreement with the work, where the influence of the 3-O-acetyl group on cytotoxicity of broader group of triterpenoides 65 -67 was studied (Mukherjee et al, 2004;Sarek et al, 2005). In the work of Chien et al, the cytotoxicity of natural 3-O-acyl derivatives of betulinic acid 68 -71 isolated from Strychnos vanprukii Craib was investigated against MEL2 line.…”
Section: Derivatization Of Betulinic Acid (1) and Betulin (3) In Posisupporting
confidence: 85%
“…This fact dramatically improves their therapeutic index for testing anti-HIV activity Fujioka et al, 1994, Mayaux et al, 1994. A comparison of activity of betulinic (1) and dihydrobetulinic acid (38) with their acetates is described in (Kim et al, 2001;Mukherjee et al, 2004). Tests with SK-MEL-2 and M14-MEL lines showed that the acetylation of hydroxyderivatives causes either a small decrease or no change in cytotoxicity (Kim et al, 2001).…”
Section: Derivatization Of Betulinic Acid (1) and Betulin (3) In Posimentioning
confidence: 99%
“…Our laboratory is focused on the search for new chemotherapy drugs for the treatment of NPC. BetA, a naturally occurring pentacyclic triterpenoid with the potential to kill melanoma cells (Pisha et al, 1995), has been shown to induce apoptosis in many cancer cell lines, including human melanoma cells, ovarian carcinomas, and leukemia HL-60 cells (Eiznhamer and Xu, 2004;Mukherjee et al, 2004). However, reports on whether or not BetA can kill NPC cell lines are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 2 can be regard as a lead for antiangiogenic agents, which deserve further exploration.The observedantiangiogenic effects of the compounds are summarized in Table 1. All the compounds [5][6][7][8][9][10] were evaluated for in-vitro cytotoxic activity of the 3b-Hydroxy-lup-20(29)-en-28-oic acid derivatives on three different tumour cell lines: ECV304, A594, MCF-7 was studied by MTT assay in triplicate. The compounds showed anticancer activity in a dose dependent manner against selected cell lines.…”
Section: Biological Activitymentioning
confidence: 99%
“…[6][7][8][9] However, among the known angiogenesis inhibitors, natural compounds such as 2-methoxyestradiol, Taxol, sulfated carbohydrates or triterpenoids have shown a tremendous potential as antiangiogenic agents. [10][11][12] Angiogenesis or Neo-vascularization is a complicated progression or development of microvascular networks by means of red blood cell perfusion. Neo-vascularization differs from angiogenesis in that angiogenesis is mainly illustrated by the projection and consequential growth of capillary buds and nurture from previously existing blood vessels.…”
Section: Introductionmentioning
confidence: 99%